Structure analysis of adiabatic film cooling effectiveness in the near field of a single inclined jet: Measurement using fast-response pressure-sensitive paint. (July 2017) - Khojasteh, Ali Rahimi; Wang, Shao Fei; Peng, Di; Yavuzkurt, Savas; Liu, Yingzheng
Highlights: Film cooling effectiveness in the jet's near field was measured by fast-response PSP. POD was used to identify signatures of energetic flow structures above the wall. At M = 0.5, the first POD mode pair reflected dominance of CRVP on the jet's near field. At M = 0.5, phase-dependent variations of CRVP and horseshoe vortex were identified. Abstract: In the present study, the film cooling effectiveness in the near field (x/D < 4) of a single inclined film-cooling jet was measured using fast-response pressure sensitive paint (fast-PSP) and a low-frame-rate CCD camera. Previous experimental data demonstrated considerable variation in this region, and good agreement was established beyond it (x/D > 4). The blowing ratios M = 0.5 and 1.0 were used. The coolant fluid was nitrogen and the air was the mainstream fluid, and both were kept at the same temperature. A fast-PSP measurement technique was used to determine the variations of the film cooling effectiveness with time. The contours of the time-averaged film cooling effectiveness demonstrated that the coolant spread on the surface throughout the near-hole region at M = 0.5, while at M = 1.0, the coolant jet detached from the surface immediately behind the hole and reattached downstream around 1.5 D behind the hole's trailing edge. The spatial distribution of the film cooling effectiveness fluctuations and its cross-correlation pattern convincingly reflected the substantial influence of the energetic unsteady flow structures in the jet and cross-flow interaction. Subsequently, the Proper Orthogonal Decomposition (POD) method was used to identify the coherent parts of the film cooling effectiveness, which are regarded as the signatures of the convective large-scale vortical structures above the wall. At M = 0.5, the near-hole region was subjected to the dominant influence of the counter-rotating vortex pair (CRVP), characterized by the first two POD modes, which contained up to 40 % of the fluctuation energy. Two signatures of large-scale symmetric structures were identified with similar energy levels. The second two POD modes corresponding to the horseshoe vortex near the leading edge of the hole were identified and contained around 10% of the fluctuation energy. Phase-dependent variations of the large-scale convective signatures in relation to the quasi-periodic CRVP and horseshoe vortex were separately detected. At M = 1.0, the signatures of the CRVP and the horseshoe vortex were also seen in the POD modes, though they were relatively difficult to distinguish.